Uang dalam Perspektif Islam - Mashur Malaka (Al-'Adl, 2009)
In Islam, economic activity history, important of him the existence of money affirmed by the opinion of Rasulullah Saw mentioning and suggesting that better commerce justice is commerce using money media dram or dinner is not a transfer of goods barterable to generate lap on the happening of transfer of different goods of a kind quality. With the existence of money, economic reality in perspective of Islam can take place better, that is looking after of and the increasing of rotation of estate velocity among human being the economic perpetrator. With the existence of money, social and economic activity earn more fluent well-held and can take place with quicker acceleration also.